Experimental Conditions and Mathematical Analysis of Kinetic Measurements Using Flow Cytometry – The FacsKin Method - Kaposi, Ambrus; Toldi, Gergely; Meszaros, Gergoo; Szalay, Balazs; Veress, Gabor; Vasarhelyi, Barna (IntechOpen, 2012)
None